2013
DOI: 10.1016/j.cmet.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Lipid Chaperone aP2 Is a Secreted Adipokine Regulating Hepatic Glucose Production

Abstract: Proper control of hepatic glucose production is central to whole body glucose homeostasis and its disruption plays a major role in diabetes. Here we demonstrate that, although established as an intracellular lipid chaperone, aP2 is in fact actively secreted from adipocytes to regulate liver glucose metabolism. Fasting and lipolysisrelated signals regulate secretion of aP2 from adipocytes, and circulating aP2 levels are markedly elevated in mouse and human obesity. Recombinant aP2 stimulates glucose production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
323
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 222 publications
(361 citation statements)
references
References 38 publications
27
323
2
3
Order By: Relevance
“…FABP4 is secreted from adipocytes under regulation by the catecholamine‐induced lipolytic signal pathway, although FABP4 lacks an N‐terminal secretory signal sequence 7, 12, 13. The present study showed that secretion of FABP4 from endothelial cells was slightly, but significantly, enhanced by stimulation of isoproterenol, similar to that in the case of adipocytes.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…FABP4 is secreted from adipocytes under regulation by the catecholamine‐induced lipolytic signal pathway, although FABP4 lacks an N‐terminal secretory signal sequence 7, 12, 13. The present study showed that secretion of FABP4 from endothelial cells was slightly, but significantly, enhanced by stimulation of isoproterenol, similar to that in the case of adipocytes.…”
Section: Discussionsupporting
confidence: 71%
“…FABP4 was secreted from HCAECs in a time‐dependent manner (Figure 2I), and the secretion of FABP4 was slightly, but significantly, enhanced in the presence of isoproterenol for 12 and 24 hours, which is known to increase secretion of FABP4 from adipocytes 12, 13. Secretion of FABP4 in the CM of Ad‐FABP4–transfected HCAECs was significantly greater than that in the CM of Ad‐Control–transfected HCAECs (Figure 2J).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations